Cyber-Terrorism: between the Globalization of Crime and the Need to Combat - Badji, Abdennour; Melek, Nassima (Journal of Legal Studies and Researches, 2022)
Cyberterrorism is a globalization crime that gives the terrorists more opportunities in the cyberspace, this study found a local legislator has criminalized the use of ICT by terrorists, and in this regard to confront the privacy of cyber-terrorism in application of international obligations, but it is not sufficient and the method of prevention must be adopted and all other acts of cyber-terrorism should be criminalized.